2017
DOI: 10.5964/jnc.v3i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Planning and self-control, but not working memory, directly predict multiplication performance in adults

Abstract: Empirical evidence suggests that working memory (WM) is closely related to arithmetic performance. WM, which is the ability to monitor and update recent information, underlies various cognitive processes and behaviors including planning, self-regulation, and self-control. However, only a few studies have examined whether WM uniquely explains variance in arithmetic performance when other WM-related domain-general factors are taken into account. In this study, we examined whether WM explains unique variance in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Shifting concerns switching between multiple tasks, operations or mental sets (Miyake et al, 2000). Working memory refers to remembering, monitoring, coding incoming information and updating information (Miyake et al, 2000;Nemati et al, 2017); and planning is related to problem solving (Laureys et al, 2021). These four EF components (i.e., inhibition, planning, shifting, working memory) will further be used in this paper to determine EF performance during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Shifting concerns switching between multiple tasks, operations or mental sets (Miyake et al, 2000). Working memory refers to remembering, monitoring, coding incoming information and updating information (Miyake et al, 2000;Nemati et al, 2017); and planning is related to problem solving (Laureys et al, 2021). These four EF components (i.e., inhibition, planning, shifting, working memory) will further be used in this paper to determine EF performance during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, one cannot assume that in the case of sale price calculations the role of the right SMG will be the same as in the case of multi-digit mental addition or subtraction (Montefinese et al, 2017). In fact, operating on familiar numbers that are often seen on shop labels (e.g., −50% or −25%) -even though they are multi-digit, and therefore, complex -may not require right-hemisphere resources such as visual working memory to the extent than does operating on unfamiliar numbers (which put greater load on memory capacity, and consequently, require critical engagement of right SMG; Rosenberg-Lee et al, 2011;Bloechle et al, 2016;Nemati et al, 2017;Mock et al, 2018). Therefore, we hypothesized that the right, as compared to left SMG, might be less critical for calculations of sale prices characteristic for consumers' daily behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Soltanlou et al (2015) revealed that verbal WM was the best predictor of multiplication performance in grade 3 (8–11 years old); however, visuospatial WM was the best predictor of multiplication performance a year later in grade 4. In general, there is agreement that WM has an integral role in math performance (Menon, 2016; but see Nemati et al, 2017).…”
Section: Introductionmentioning
confidence: 99%